Comparison of MMP-9 Inhibition Activities of Phenolic Acids of Sandoricum koetjape Leaves by Molecular Docking - Susy Saadah; Silvester Tulandi; Randi Rohman (Shiraz University of Medical Sciences, 2023)
Sandoricum koetjape has been used for generations in traditional Indonesian medicine. The leaves were used to treat helminthiasis, cough, stomachache, diarrhea, bloating, leucorrhoea, colic, and fever in Indonesia. Identification of phenolic acids in the Sandoricum koetjape leaves was done by ultrahigh-pressure liquid chromatography (UPLC). Gallic acid, 4-hydroxybenzoic acid, chlorogenic acid, caffeic acid, syringic acid, p-coumaric acid, and ferulic acid were identified as phenolic acids found in Sandoricum koetjape leaf extracts. Heart disease, stroke, and cancer are the three noncommunicable diseases that kill the most people in Indonesia. Coronary artery disease, cardiovascular disease, cardiomyopathy, cancer, tumor, type 2 diabetes, and cholesterol have all been linked to MMP-9. This study aimed to determine the phenolic acids contained in the leaves of Sandoricum koetjape and to determine their inhibitory activity against the matrix metalloproteinase-9 (MMP-9). Molecular docking studies were carried out by the autodock 4.2 program integrated with the pyrx v.09.8 virtual screening tool. The chlorogenic acid in Sandoricum koetjape leaf extract binds more strongly than the other phenolic acids. Interacting between chlorogenic acid with MMP-9 on amino LEU187, LEU188, ALA189, HIS405, and TYR423. AdmetSAR and Protox II databases were used for physiochemical and ADMET properties. Chlorogenic acid is expected to have high oral bioavailability in humans, good intestinal absorption, and an equivalent distribution in the intestine and blood plasma. Chlorogenic acid's acute toxicity is also expected to be low. Chlorogenic acid is also non-toxic to the liver, immune system, mutagenic, and cytotoxic. Sandoricum koetjape phenolic acid, particularly chlorogenic acid, appeared to be an efficient MMP-9 inhibitor based on docking results.